Clinico-Hematological Spectrum of Non-Leukemic Myeloproliferative Disorder - Akbar, Ahtasham; Afshan MD, Roshan; Asif, Muhammad; Shah, Pir Sabir; Zhaira, Dua (Biological and Clinical Sciences Research Journal, 2025)
Myeloproliferative neoplasms (MPNs) are a group of hematological disorders originating from marrow stem cells, characterised by clonal proliferation of hematopoietic components. The three primary non-leukemic MPNs include Polycythemia Vera (PV), Essential Thrombocythemia (ET), and Primary Myelofibrosis (PMF). These disorders affect the bone marrow, liver, and spleen, leading to various clinical manifestations. Limited data on MPNs in Pakistan necessitates further research to understand their prevalence and demographic distribution. Objective: To assess the spectrum, prevalence, and demographic distribution of non-leukemic MPNs among patients at Benazir Bhutto Hospital, Rawalpindi. Methodology: A retrospective study was conducted over three to four months at Benazir Bhutto Hospital, Rawalpindi. Patient data were analysed using SPSS Version 25, focusing on categorical variables such as age, gender, and MPN type. The diagnosis of MPNs was based on clinical, hematological, and cytogenetic criteria by the 2016 WHO classification. Results: 26 patients were diagnosed with non-leukemic MPNs, with a male-to-female ratio of 1.4:1. Among these, 15 males (58%) and 11 females (42%) were affected. Polycythemia Vera was diagnosed in 7 patients (27%), Essential Thrombocythemia in 9 patients (35%), and Primary Myelofibrosis in 7 patients (27%). Three patients (11%) were classified as MPN-Unclassified. Conclusion: The study highlights the demographic distribution and prevalence of non-leukemic MPNs in a tertiary care hospital in Pakistan. These findings emphasise the need for clinical and hematological evaluations and cytogenetic testing for accurate diagnosis. Further genetic and environmental studies are required to explore regional MPN prevalence and pathogenesis variations.